Theological Accessibility: The Contribution of Disability - Creamer, Deborah (Disability Studies Quarterly, 2006)
Religious institutions and communities that have embraced the cause of disability have invested a great deal of energy in struggles against architectural barriers, including the elevated pulpit. Valuing this engagement but also recognizing that access to physical space is only a first step in a project of accessibility, this paper claims that it is time to open the entire breadth of religious traditions to an "accessibility audit." Not only does such an examination highlight potential barriers — challenges of scripture and metaphor, for example — but it also suggests new theological possibilities in which disability is not simply a consumer or an evaluator of tradition but rather a constructive element that offers new options for theological reflection. This paper briefly reviews the disability theology models that have been offered to date (the Accessible God by Jennie Weiss Block, the Inclusive God by Kathy Black, and the Disabled God by Nancy Eiesland), highlighting ways in which these proposals make significant contributions to the breadth and depth of Christian theological reflection. This analysis shows that the value of disability theology is confined neither to people with disabilities nor to the arena of religion, but rather, as has been the case with other liberation theologies, has the potential to affect wider worlds and fields of study as well.